A novel transgenic zebrafish line allows for in vivo quantification of autophagic activity in neurons. Issue 8 (3rd August 2019) - Khuansuwan, Sataree; Barnhill, Lisa M.; Cheng, Sizhu; Bronstein, Jeff M.
ABSTRACT: The pathophysiology of most neurodegenerative diseases includes aberrant accumulation of protein aggregates. Recent evidence highlights the role of protein degradation pathways in neurodegeneration. Concurrently, genetic tools have been generated to enable zebrafish, Danio rerio, to be used as an animal model to study neurodegenerative processes. In addition to optical clarity and fast ex utero development, the zebrafish brain is relatively small and has conserved structures with its mammalian counterparts. To take advantage of this model organism and to aid further studies on autophagy and neurodegeneration, we created a stable transgenic zebrafish line that expresses eGFP-Map1lc3b specifically in post-mitotic neurons under the elavl3 promoter. This line is useful for indirectly monitoring autophagic activity in neurons in vivo and screening for macroautophagy/autophagy-modulating compounds. We determined the applicability of this transgenic line by modulating and quantifying the number of autophagosomes via treatment with a known autophagy inducer (rapamycin) and inhibitors (3-methyladenine, protease inhibitors). Additionally, we proposed an in vivo method for quantifying rates of autophagosome accumulation, which can be used to infer occurrence of autophagic flux. Last, we tested two FDA-approved drugs currently undergoing clinical studies for Parkinson disease, isradipine and nilotinib, and found that isradipine did not modulate autophagy, whereas nilotinib induced both autophagosome number and autophagic flux. It is hoped that others will find this line useful as an in vivo vertebrate model to find or validate autophagy modulators that might be used to halt the progression of neurodegenerative diseases. Abbreviations: 3MA: 3-methyladenine; BafA: bafilomycin A1; dd: dorsal diencephalon; dpf: days post fertilization; e: eye; eGFP: enhanced green fluorescent protein; Elavl3: ELAV like neuron-specific RNA binding protein 3; FDA: Food and Drug Administration; hb: habenula; hpt, hours post treatment; Map1lc3b: microtubule-associated protein 1 light chain 3 beta; nt: neural tube; ot, optic tectum; P/E: pepstatin A and E64d; PD: Parkinson disease; PMTs: photomultiplier tubes; PTU: 1-phenyl-2-thiourea; Ta: annealing temperature; Tel, telencephalon